2013
DOI: 10.1080/21568235.2013.772352
|View full text |Cite
|
Sign up to set email alerts
|

Societal production and careers of PhDs in chemistry and biochemistry in France and Japan

Abstract: International audienceUntil quite recently, in all of the industrialised countries, PhD students were educated to form the elite and the managerial class of universities and public research bodies. Their careers depended primarily on the academic labour market. Since the late 1980s, the "production of PhDs" has become a much-discussed economic and social issue, and the thinking, reforms and tensions surrounding this category of graduates have gathered momentum. Vocational fields and the contents of the PhDs' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A majority of scholars think that a Ph.D. degree is limited to having careers in academics. However, many other fields require Ph.D. degree holders [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. We have collected some information about the career prospects for scholars once scholars complete the Ph.D. program as listed below.…”
Section: Careers For Phd Holdersmentioning
confidence: 99%
“…A majority of scholars think that a Ph.D. degree is limited to having careers in academics. However, many other fields require Ph.D. degree holders [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. We have collected some information about the career prospects for scholars once scholars complete the Ph.D. program as listed below.…”
Section: Careers For Phd Holdersmentioning
confidence: 99%
“…For example, a study in France found that post‐doctoral experience is beneficial to secure an academic position at a public research institute. However, the very same experience is seen as an impediment to being employed in the industry 7 . It seems less challenging for PhD biochemistry graduates to find professional jobs and managerial positions linked to large corporations, often combining academic research and employment in the private sector through established networks of collaboration between academia and the industry 7 …”
Section: Introductionmentioning
confidence: 99%
“…7 It seems less challenging for PhD biochemistry graduates to find professional jobs and managerial positions linked to large corporations, often combining academic research and employment in the private sector through established networks of collaboration between academia and the industry. 7 The question arises: Are biochemistry graduates employable in a South African society? Are biochemistry graduates equipped with the necessary employability skills alongside their subject-specific skills to secure employment after graduation?…”
Section: Introductionmentioning
confidence: 99%